2014
DOI: 10.1128/cvi.00700-13
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Mycobacterium bovis BCG Vaccination Confers Dose-Dependent Superior Protection Compared to That of Subcutaneous Vaccination

Abstract: e Worldwide, the Mycobacterium bovis BCG vaccine is one of the most widely used vaccines. However, it appears to be ineffective in preventing pulmonary tuberculosis. Here, we show that pulmonary BCG vaccination of mice with a broad dose range provides superior protection against Mycobacterium tuberculosis challenge compared to that of subcutaneous vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…For example, consistent with short-term studies by Aguilo et al, Chen et al, and Giri et al, who showed that pulmonary administration of BCG was superior to the s.c. route in terms of protection in the lungs at early time points postvaccination, our pulmonary protection results were significantly better for the i.n. route than for the s.c. route at 2 and 4 months postvaccination (14,16,27). However, no differences in lung postchallenge protective responses were seen at 8 and 10 months postvaccination.…”
Section: Discussionmentioning
confidence: 72%
“…For example, consistent with short-term studies by Aguilo et al, Chen et al, and Giri et al, who showed that pulmonary administration of BCG was superior to the s.c. route in terms of protection in the lungs at early time points postvaccination, our pulmonary protection results were significantly better for the i.n. route than for the s.c. route at 2 and 4 months postvaccination (14,16,27). However, no differences in lung postchallenge protective responses were seen at 8 and 10 months postvaccination.…”
Section: Discussionmentioning
confidence: 72%
“…BCG revaccination regimens using a primary and secondary ID vaccination have been shown to enhance protection against pulmonary M. bovis infection in cattle [13], provide improved early protection against M.tb in mice [14] and moderate improvements in protection against M.tb infection in people [15], [16]; these improvements were dependant on geographical location of the study cohort. Murine studies suggest immunisation delivered directly to the respiratory mucosa may provide a more effective route of vaccination [17], [18] and have indicated that intranasal delivery of a second BCG vaccination improved the outcome of M. tb challenge compared to a single ID BCG vaccination [19]. These studies taken together suggest that the efficacy afforded by multiple applications of BCG are improved by delivery of the second BCG vaccination to the lung.…”
Section: Introductionmentioning
confidence: 95%
“…However, one of the shortcomings of s.c. BCG administration is the overall weak memory lymphocyte generation, which in addition lacks the mucosal-homing chemokine receptors that allow migration to the lung (9). Hence, mucosal vaccination has been suggested as a mimic of natural infection in order to improve local immunity at the site of infection (1012). Comprehensive analyses of local immunity and correlates of protection in both the lung airways and the parenchyma are essential for the rational design of mucosal TB vaccination strategies using BCG (13, 14).…”
Section: Introductionmentioning
confidence: 99%